The world of the polar bear - Rosing, Norbert (Richmond Hill, Ont. : Firefly Books, 2006)
Written by an acclaimed nature photographer and featuring 175 remarkable color photographs this is a season-by-season account of the life of polar bears, including hunting, mating, rearing cubs, and journeying to and from the ice. A powerful predator, revealed here by an acclaimed nature photographer. The polar bear is the largest terrestrial carnivore, uniquely adapted to thrive in the harsh environment of the Far North. In The World of the Polar Bear, renowned nature photographer Norbert Rosing follows the polar bear through each season. With its thorough and engaging text and spectacular photography, the book provides:- A season-by-season account of the life of the polar bear, including feeding, mating, rearing of cubs and journeying from the ice- An intimate look at the animals that share the polar bear's environment, including seals, arctic foxes, walruses and muskoxen- A section on such northern sky phenomena as sun dogs and the northern lights- Many anecdotes and insights about the polar bear -- at once a loving parent, a fierce predator and a natural jester .In addition to the 175 truly remarkable color photographs, there are four spectacular gatefolds. The World of the Polar Bear will appeal to any reader interested in natural history, animals, and the Arctic. Polar bears are seriously threatened by global warming, and this book will attract considerable press attention.
Spring: Polar bear's den -- Journey to the ice -- Arctic Spring -- Summer: Ice breakup -- Searching for the Arctic Fox -- Surprise visitor -- Fall: More close encounters -- Waiting for the ice to form -- Leaving the land -- Winter: Adapting to the Arctic -- Sky phenomena -- Habitat of ice and snow -- Afterword -- On wildlife photography -- Technical information -- Polar bear facts and figures -- Map -- Acknowledgments -- Bibliography -- Index.
"A Firefly book"--T.p. verso.
Includes bibliographical references (p. 201) and index.
Keywords: Polar bear; Polar bear -- Pictorial works